ANALISIS YURIDIS PENGHINAAN KEPALA NEGARA DALAM RANCANGAN KITAB UNDANG-UNDANG HUKUM PIDANA - Prasetyo Hadi Prabowo (LPPM Universitas Bina Bangsa, 2023)
The rules for insulting the head of state contained in the Draft Criminal Code have attracted a lot of attention from the people in Indonesia, thus raising the pros and cons. The decision of the Constitutional Court which declared article 134 unconstitutional, made several legal observers compare the article on the regulation of insulting the head of state contained in the Criminal Code Bill with article 134 of the Criminal Code. Broadly speaking, there are two differences between the regulation of insulting the head of state in the Draft Criminal Code and Article 134 of the Criminal Code. First, the Criminal Code Bill regulates in more detail the humiliation of the head of state. Second, there are differences in the application of the offense of insulting the head of state. Insult to the head of state is considered not to fulfill justice, this is because the regulation on insulting the head of state is contrary to Article 27 and 28 of the 1945 Constitution of the Republic of Indonesia. In addition, humiliation is a form of violation that can reduce basic rights. Therefore, there should be no special application to the head of state